2016
DOI: 10.3390/ijerph13100928
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Drivers of PM2.5 in the Accumulation Phase of Air Pollution Episodes in the Yangtze River Delta of China

Abstract: Recent studies in PM2.5 sources show that anthropogenic emissions are the main contributors to haze pollution. Due to their essential roles in establishing policies for improving air quality, socioeconomic drivers of PM2.5 levels have attracted increasing attention. Unlike previous studies focusing on the annual PM2.5 concentration (Cyear), this paper focuses on the accumulation phase of PM2.5 during the pollution episode (PMAE) in the Yangtze River Delta in China. This paper mainly explores the spatial variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…This suggests that human activities might be the dominant factor affecting PM 2.5 concentrations in Jinjiang, China, which is consistent with previous research [50]. Of the anthropogenic factors, we found that population density was most responsible for enhancing the effects of elevation and dominant tree species on PM 2.5 concentrations.…”
Section: Interactive Functionssupporting
confidence: 81%
“…This suggests that human activities might be the dominant factor affecting PM 2.5 concentrations in Jinjiang, China, which is consistent with previous research [50]. Of the anthropogenic factors, we found that population density was most responsible for enhancing the effects of elevation and dominant tree species on PM 2.5 concentrations.…”
Section: Interactive Functionssupporting
confidence: 81%
“…The Yangtze River Delta (YRD) is the region of eastern China with the most developed economy, the greatest degree of urbanization and high coal consumption [8]. The region has suffered frequent extreme haze episodes in recent years [9]. Therefore, understanding the characteristics and its driving factors of PM 2.5 concentrations will be of benefit in the task of regional pollution prevention and control.…”
Section: Introductionmentioning
confidence: 99%
“…It can detect the spatial stratified heterogeneity of dependent variables and reveal the driving force behind it with its great flexibility [18]. It has been widely used in various fields, such as natural and social sciences [19][20][21], environmental pollution [22,23] and disease risk detection [16,24], etc., but it is rarely used in the field of LE research.Therefore, we analyzed the spatial distribution characteristics of LE by descriptive methods and spatial autocorrelation analysis. Then we used the Geographical Detector technique to reveal the impact of social and environmental factors and their interactions on LE as well as their optimal range for the maximum LE level, providing reference for the research on LE, economic and educational development, utilization of medical resources, environmental protection as well as population management policy-making in China.…”
mentioning
confidence: 99%
“…It can detect the spatial stratified heterogeneity of dependent variables and reveal the driving force behind it with its great flexibility [18]. It has been widely used in various fields, such as natural and social sciences [19][20][21], environmental pollution [22,23] and disease risk detection [16,24], etc., but it is rarely used in the field of LE research.…”
mentioning
confidence: 99%